Trilhares da alfabetização na educação infantil: um estudo sobre a proposta do pacto nacional pela alfabetização na idade certa - Menarbini, Andreia (2020)
In Brazil, the literacy of children raises pertinent and current issues to be researched, due to the complexity of this theme and the alarming results presented. The Ministry of Education, for the first time in the history of public literacy policies, included, in a large-scale program, the participation of Early Childhood Education (ECE) teachers. This research aimed to analyze the conceptions of teachers about the literacy proposal of the National Pact for Literacy at the Right Age for Early Childhood Education, its inclusion in the PNAIC, and its influences on their professionalism. As specific objectives were established, to know the meaning that is attributed to “literacy in Early Childhood Education” in the PNAIC proposal; to identify conceptions of teachers about the PNAIC literacy proposal for ECE; to identify the literacy actions of ECE teachers, PNAIC students, of the Municipal Network of Santo André; to infer if there are contradictions in the PNAIC proposal and the literacy practices carried out by teachers in ECE. The problem of this study arose from the teaching trajectory of the researcher at the public school, and her research carried out in the Professional Master of Education. As for the theoretical framework, the model was adopted in line with the post-critical theories, whose influences go back to the critical theory, which contributed to the reflection and discussion of the following categories: Literacy, Early Childhood Education, Teacher Training, PNAIC. The methodology chosen for the research was a qualitative and quantitative approach, and the data collection instruments were the questionnaire, related to training and professional performance, and a semi-structured interview with teachers, in addition to the collection of documents and publications on literacy, reading and writing, and the PNAIC. The collected information was analyzed using different techniques, the quantitative data being subjected to statistical and descriptive analysis, and those of the qualitative approach analyzed using the speech analysis technique. The research results show that the conception of teachers about the PNAIC proposal for ECE is not unique, it differs according to the self-conception of literacy and is revealed in the pedagogical practice corresponding to their personal, academic, and professional path, constituted in their professionalism. Regarding the meaning of literacy for ECE in the PNAIC proposal, we emphasize that it is related to the processes of appropriation of written culture as a right of children, respecting the characteristics of childhood. When it comes to literacy in ECE, all wisdom is needed so that respect for children prevails in all proposals and actions, so that the rights of the child are guaranteed considering all aspects related to it. Therefore, it must be considered that literacy as a formal and mechanical act of learning the alphabet and its use as a communication code should not happen in ECE. At this stage, the work should focus on the development of different languages, including reading and writing, as a form of child expression and interactions to understand the world around them, according to the culture in which the child is inserted and their own interests.